Identifikasi Pelaksanaan Penilaian Sikap Pada Pembelajaran Ipa Kurikulum 2013 Kelas VIII Semester Genap Di SMP Swasta Surakarta Tahun Ajaran 2014/2015 - Mutohharoh, Anis, Dra. Hariyatmi, M.Si (2015)
Curriculum 2013 is a learning that emphasize on the affective aspect, which is the behavior changing. A teacher should be able and understand the process of assessing. One of them is the behavior assessment. This research is intended to find out the implementation of behavior assessment in science learning by the 8th grade teachers in second semester curriculum 2013 in SMP Swasta Surakarta in academic year 2014/2015. This research used qualitative descriptive design, the data collection was done with the documenter study technique that was behavior assessment instrument in lesson plan made by the science teachers, observation of behavior assessment implementation in the science learning process in second semester in academic year 2014/2015, and also interview with the science teachers about the behavior assessment, then analyzed by descriptive statistic. The result showed that the teachers' ability in arranging behavior assessment instrument by observation technique was 72.2%, self assessment technique was 68.03%, peer assessment technique was 69.55%, all three were included in good category and journal technique was included in very poor category (22.2%). For the teachers' ability in the implemenattion of behavior assessment in science learning process, for observation technique was 83.86%, self assessment technique 58.33%, peer assessment technique 58.33%, all three were included in good category. Meanwhile, journal category was included in very poor category which was 0%. Therefore, it can be concluded that the teachers' ability in arranging behavior assessment instrument in lesson plan was good (57.9%) and observation of behavior assessment implementation in the process of science learning was included in poor category (45.13%).